Legal Protection for Victims of Crime with Forced Defense According to Law Number 1 of 2023 of the Criminal Code - Anggraeni Puspitarini; Didik Suhariyanto; Gradios Nyoman Tio Rae (SEAN Institute, 2026)
Law enforcement often shows inconsistencies, where victims of crimes who commit forced defense (Noodweer) can actually become suspects or defendants who cause legal uncertainty and a sense of injustice. This study aims to analyze legal protection and legal justice for victims who are also perpetrators of forced defense crimes. This study specifically highlights Decision Number 1225/ Pid.B /2020/PN- Jkt.Sel , where a wife who stabbed her husband in a situation of threat of physical and verbal violence was sentenced to 4 years in prison for alleged persecution that caused death (Article 351 paragraph (3) of the Criminal Code). The Panel of Judges argued that the defendant's actions could not be categorized as forced self-defense. The research method used is normative juridical law using legislative, conceptual, analytical, and case approaches. The scope of this research is legal protection for victims of criminal acts who commit forced defense (Noodweer) in the perspective of the old Criminal Code (KUHP) and Law Number 1 of 2023 concerning the new Criminal Code (especially Articles 34 and 43). The results of the study show that the defendant's actions were carried out because of force and there was a mental shock constituting a forced defense (noodweer ). The conclusion is that there is a reason for the pardon and the defendant should not be subject to criminal charges as specified in Article 49 Paragraph 1 of the Criminal Code.